Gospel: Blessing to Cultures - Marangattu , Jacob (Asian Horizons, 2023)
The primary invitation of God to the whole of creation is to be in a blessed and happy state of existence. This primeval joy and happiness ordered by God was ruptured by human sin which shook the harmonious existence among the three matrices of reality: God, humans and the cosmos. But God entered into human history by incarnating as a cultural person to lead creation back to its original blessedness. The Gospel of Jesus Christ is the divinely-devised blue print to assist humans in this regard. The article shows how cultures that accept the Biblical world view achieve a better record of value consciousness as well as progress in economic and scientific pursuits.